May BDNF be implicated in the exercise-mediated regulation of inflammation? critical review and synthesis of evidence - Papathanassoglou, Elizabeth; Miltiadous, Panagiota; Karanikola, Maria (My University, 2014)
Introduction: Exercise attenuates inflammation and enhances levels of brain-derived neurotrophic factor (BDNF). Exercise also enhances parasympathetic tone, although its role in activating the cholinergic anti-inflammatory pathway is unclear. The physiological pathways of exercise’s effect on inflammation are obscure. Aims: To critically review the evidence on the role of BDNF in the anti-inflammatory effects of exercise and its potential involvement in the cholinergic anti-inflammatory pathway. Methods: Critical literature review of studies published in MEDLINE, PubMed, CINAHL, Embase, and Cochrane databases. Results: BDNF is critically involved in the bidirectional signaling between immune and neurosensory cells and in the regulation of parasympathetic system responses. BDNF is also intricately involved in the inflammatory response: inflammation induces BDNF production, and, in turn, BDNF exerts pro- and/or anti-inflammatory effects. Although exercise modulates BDNF and its receptors in lymphocytes, data on BDNF’s immunoregulatory/anti-inflammatory effects in relation to exercise are scarce. Moreover, BDNF increases cholinergic activity and is modulated by parasympathetic system activation. However, its involvement in the cholinergic antiinflammatory pathway has not been investigated. Conclusion: Converging lines of evidence implicate BDNF in exercisemediated regulation of inflammation; however, data are insufficient to draw concrete conclusions. We suggest that there is a need to investigate BDNF as a potential modulator/mediator of the anti-inflammatory effects of exercise and of the cholinergic antiinflammatory pathway during exercise. Such research would have implications for a wide range of inflammatory diseases and for planning targeted exercise protocols.
Keywords: Brain-derived neurotrophic factor; Physical activity; Early progressive mobility; Exercise; Inflammation; Immunity; Critical illness; Parasympathetic nervous system; Cholinergic anti-inflammatory pathway